The role of planfulness for well-being, stress, and goal disruption during COVID-19 - Ameden, Wesley C.; Tricomi, Elizabeth; Heintzelman, Samantha J. (Frontiers in Psychology, 2024)
Planfulness refers to an individual's tendency to be future oriented, mentally flexible, and cognitively strategic when engaging with goals, and has been shown to predict goal completion. We investigated the relationships among planfulness, goal disruption, stress, and psychological well-being during the COVID-19 pandemic, which served as a unique setback context. We measured these constructs using the Planfulness Scale, an ad-hoc survey item probing goal disruption in the pandemic, the Perceived Stress Scale, and the Warwick-Edinburgh Mental Wellbeing Scale, respectively. Participants were university students (N = 174; mean age 23.03, SD: 4.37; 77% female). Higher planfulness predicted lower goal-disruption, lower stress, and higher well-being during the pandemic, extending its benefits beyond the goal domain. High levels of planfulness did not protect against goal disruption among those participants in which the self-reported personal impact of the pandemic was highest. Differences in goal disruption across levels of planfulness were constrained to lower reported pandemic impact. However, the differences in psychological well-being and stress by levels of planfulness were retained even when self-reported perceptions of personal pandemic impact were high. More planful students maintained lower stress and higher psychological well-being than their less planful peers across levels of adversity. These findings suggest that even in extremely difficult contexts in which planfulness does not protect against goal disruption, it still confers personal benefits in terms of psychological health. Moved down [1]: The current study was part of a larger project 223 investigating the effects of the pandemic on goal-related and mental 224 health outcomes in undergraduate students. This larger project took 225 place over two semesters (Fall, 2020 and Spring, 2021) with separate 226 cohorts of students. None of the variables of interest differed 227 significantly between the two samples as measured using 228